Computational analysis of radiative Williamson hybrid nanofluid comprising variable thermal conductivity. (2nd August 2021) - Zubair, Tamour; Usman, Muhammad; Hamid, Muhammad; Sohail, Muhammad; Nazir, Umar; Nisar, Kottakkaran Sooppy; Vijayakumar, Velusamy
Abstract: This article demonstrates the study of thermal energy with the rheology of Williamson liquid over a rotating surface. The correlations between nanoparticles and hybrid nanoparticles in the base fluid are considered to determine the comparative analysis in nanoparticles and hybrid nanostructures. The variable terms are thermal conductivity and thermal radiation, which are also inserted in the energy equation with the associations of nano and hybrid nanoparticles. The ordinary differential equations (ODEs) are generated from the modeled problem using transformation. In contrast, the least square method is used to simulate analytic solutions of required ODEs, and further results are compared with a numerical scheme. The simulations of temperature and motion of fluid particles are performed in graphs and tables. The reduction in motion of fluid particles is captured versus the variation of Williamson number and magnetic number. At the same time, Williamson's number and magnetic parameter also reduce momentum boundary layer thickness. The hybrid nanoparticles play a vital impact on producing a high rate of acceleration in flow, and hybrid nanoparticles are useful to produce maximum energy compared to nanostructures.